"dy\/dx=y'"
"d^2y\/dx^2=y''"
"(1+x)\u00b2 y'' + (1+x) y' + y = 4 \\cos (\\ln(1+x))"
Let's introduce the change of variable:
"1+x=e^t"
"t=\\ln(1+x)"
"dt\/dx=1\/(1+x)=e^{-t}"
"\\dot {y}=dy\/dt"
"\\ddot {y}=d^2y\/dt^2"
"y'=\\dot{y} e^{-t}"
"y''=(\\ddot{y} -\\dot{y})e^{-2t}"
So,
"\\ddot{y}+\\dot{y}+y=4\\cos t"
We obtained nonhomogeneous linear differential equation of the second order. The general solution of this nonhomogeneous equation is the sum of the general solution "y_0" of the related homogeneous equation and a particular solution "y_1" of the nonhomogeneous equation: "y=y_0+y_1".
Related homogeneous differential equation:
"\\ddot{y}+\\dot{y}+y=0"
Its characteristic polynomial is "r^2+r+1". Discriminant "D=1^2-4 \\cdot 1 \\cdot 1=-3". So, the characteristic polynomial has two complex conjugate roots "\\frac{-1\u00b1i \\sqrt{3}}{2 \\cdot 1}=-1\/2\u00b1i \\sqrt{3}\/2" and the general solution of homogeneous differential equation is "y_0=e^{-t\/2}(C_1 \\cos (\\sqrt{3}\/2 \\cdot t) + C_2 \\sin (\\sqrt{3}\/2 \\cdot t))".
Particular solution of the nonhomogeneous equation can be written in the form "y_1=A \\cos t+B \\sin t", where A and B - undetermined coefficients.
"\\dot{y_1}=-A \\sin t+B \\cos t"
"\\ddot{y_1}=-A \\cos t - B \\sin t"
Let's substitute these values into "\\ddot{y}+\\dot{y}+y=4\\cos t":
"-A \\cos t - B \\sin t - A \\sin t+B \\cos t + A \\cos t + B \\sin t = 4 \\cos t"
"B \\cos t - A \\sin t = 4 \\cos t"
"\\begin{cases}\nA=0 \\\\\nB=4\n\\end{cases}"
"y_1=4 \\sin t"
So, "y=y_0+y_1=e^{-t\/2}(C_1 \\cos (\\sqrt{3}\/2 \\cdot t)+ C_2 \\sin (\\sqrt{3}\/2 \\cdot t))+4 \\sin t"
The final answer can be obtained after the return to the variable x:
"y=e^{-\\frac{\\ln(1+x)}{2}}(C_1 \\cos (\\sqrt{3}\/2 \\ln(1+x) )+ C_2 \\sin(\\sqrt{3}\/2 \\ln(1+x)))+4 \\sin (\\ln(1+x))"
Answer: "y=e^{-\\frac{\\ln(1+x)}{2}}(C_1 \\cos (\\sqrt{3}\/2 \\ln(1+x) )+ C_2 \\sin(\\sqrt{3}\/2 \\ln(1+x)))+4 \\sin (\\ln(1+x))"
Comments
Leave a comment